2006
DOI: 10.2353/ajpath.2006.051098
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Proteinase-Activated Receptor 2 Activation on Motility Impairment and Tissue Damage Induced by Intestinal Ischemia/Reperfusion in Rodents

Abstract: We hypothesized that proteinase-activated receptor-2 (PAR 2 ) modulates intestinal injuries induced by ischemia/reperfusion. Ischemia (1 hour) plus reperfusion (6 hours) significantly delayed gastrointestinal transit (GIT) compared with sham operation. Intraduodenal injection of PAR 2 -activating peptide SLIGRL-NH 2 significantly accelerated transit in ischemia/reperfusion but not in sham-operated rats. GIT was significantly delayed in ischemia/reperfusion and sham-operated PAR 2 ؊/؊ mice compared with PAR 2 ؉… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
38
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 63 publications
0
38
1
Order By: Relevance
“…on the other hand, a recent study demonstrated that intraduodenal injection of the Par-2-activating peptide SliGrl-nH(2) may inhibit the intestinal damage and improve the delayed gastrointestinal transit induced by intestinal i/r (20). However, it remains unclear whether the functional blocking of Par-2 exacerbates intestinal i/r injury.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…on the other hand, a recent study demonstrated that intraduodenal injection of the Par-2-activating peptide SliGrl-nH(2) may inhibit the intestinal damage and improve the delayed gastrointestinal transit induced by intestinal i/r (20). However, it remains unclear whether the functional blocking of Par-2 exacerbates intestinal i/r injury.…”
Section: Introductionmentioning
confidence: 97%
“…Several studies have reported that Par-2 mediates the protective effect against myocardiac or intestinal i/r injury (20,(40)(41)(42). These reports indicate that Par-2 activation with a Par-2-activating peptide administered to animal models reduces I/R-induced tissue damage.…”
Section: A B Bmentioning
confidence: 99%
“…Previous research has shown that mesenteric I/R not only produces mucosal damage, but also induces alterations of intestinal motor activity with a delay in the gastrointestinal transit time. [30][31][32] These alterations can be the result of structural and neuronal changes occurring within the enteric nervous system, which may play a role in the progress of bacterial overgrowth with subsequent translocation caused by inadequate bacterial clearance. 30,33,34 The administration of Tempol signifi cantly decreased histological damage (Table 3) and PMN infi ltration in intestinal tissue specimens when compared with the I/ R-treated animals (group 2).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent in vivo study examining the protective effect of SL-NH 2 against intestinal injury caused by ischemia-reperfusion, it was shown that mast cell activation was involved in the underlying mechanism of protection [7]. PAR2 is expressed on cardiac mast cells and activation leads to mast cell degranulation and the release of various biologically active mediators including TNFα [8,9].…”
mentioning
confidence: 99%